Enhancement of Extender Excellence of Frozen Bull Semen Using α-Tocopherol as an Antioxidant - Ullah, Zakir; Khan, Hamayun; Hussain, Syean Maryam; Tarique Tunio, Muhammad; Raihan Dilshad, Syed Muhmmad; Gohar, Ali; Zahid, Hafsa; Ali, Abid (Acta Scientiae Veterinariae, 2019)
Background: Addition of the antioxidant to extender media is the most appropriate attempt to reduce structural losses encounter during the process of cryopreservation. Hence semen excellence could be maintained for longer duration without adverse impact. Additionally antioxidants are not only capturing the reactive oxygen species but also improve the sperm quality indicators and fertility. Accordingly, current elucidation has been executed to explore the dose depended appraisal of varied concentration of α-tocopherol in Tris-based extender on frozen-thawed bull semen quality parameters for enhancement of bull semen cryopreservation in the subtropical ecosystem of Peshawar. Materials, Methods & Results: Experiments were carried out on semen that has been collected from both Achai-an indigenous breed and Holstein Friesian (HF) - the exotic breed in artificial vagina maintained at 42°C from the experimental bulls of either breed and processed independently breed wise. Semen specimens with above 70% motility were evaluated separately breed-wise under same environmental condition. Standard procedure was adopted to extend the collected semen in the experimental extenders and frozen subsequently. After thawing, further Analysis of the frozen straws of semen was carried out for sperm excellence indicators that include motility, viability, acrosomal integrity and functional integrity of spermatozoa under the subtropical condition. Sperm viability and acrosomal integrity were determined by dual staining procedure i.e. Trypan-blue and Giemsa stains. The hypo-osmotic swelling (HOS) test was used to assess plasma membrane integrity. The current elucidation demonstrated that α-tocopherol 1.5 mg/mL supplemented in extender had significantly (P < 0.05) increased sperm excellence gauge that includes motility, viability, acrosomal integrity and functional membrane integrity in both the breeds. On the other hand, the result further elucidated those concentrations higher or lower than 1.5-1 mg/mL α-tocopherol supplemented in the present study resulted in a lower semen functional attributes subsequent to freezing. Discussion: Biological samples were preserved by various methods such cryopreservation at low temperature to maintain them intact and facilitate downstream experiments. Antioxidants were associated with the chemical breakage of the substrate consequential from oxidation and counterbalance the free radicals thus diminish the damaging impacts to spermatozoa in cryopreservation. There is lack of data with respect to lipid peroxidation and cell reinforcement limit in cryopreserved semen, and cryopreservation is related with the generation of receptive oxygen species (ROS) which lead to lipid peroxidation (LPO) of sperm membranes, bringing about lost motility, viability and fertility of sperm. Recently, in the reproductive management of the dairy animals, an important focus of research is to overcome the deleterious impact associated with semen cryopreservation. Elucidation of differential dose depended expression of α-tocopherol in semen extender has been evident in this study. The results were corroborated with diverse mammalian species under varied ecological management setups. Furthermore the detrimental impact of high doses of α-tocopherol in the semen extender has been demonstrated. It was deduced from the current finding that addition of α-tocopherol via dose depended approach in Tri extender enhanced the cryosurvivability of both Achai indigenous breed and HF the exotic breed, under existing reproductive management in the local ecosystem of Peshawar.